Catalysing Global Peace Through The Strengthening Of Forensic Science Application In Shari'ah Law - Baharuddin, AS; Ahmad, MH; Harun, MAW; Wan Abdul Fattah Wan Ismail; Lukman Abdul Mutalib (International Islamic University Malaysia (IIUM), 2024)
Indexed by WOS